Pengaruh Starlink terhadap Strategi Business Continuity Plan pada Perusahaan Internet Service Provide di Indonesia - Mauliyanto, Mauliyanto; Sendjaja, Theodorus (Jurnal Informatika dan Bisnis, 2025)
The Business Continuity Plan (BCP) is a vital element in maintaining the operational continuity of Internet Service Providers (ISPs), especially in Indonesia, which faces complex geographical and infrastructural challenges. In this context, the presence of Starlink, a low Earth orbit (LEO) satellite-based internet service provider, presents new opportunities for ISPs to develop more adaptive and resilient BCP strategies in the face of disruptions. This literature study aims to analyze the potential impact of Starlink integration within the BCP framework of Indonesian ISPs, based on a review of various scientific publications, technical reports, and regulatory documents. The study finds that Starlink offers advantages in terms of network recovery speed, coverage of remote areas, and integration flexibility as a backup connectivity solution. However, challenges related to cost, regulations, and cybersecurity must be taken into account in long-term planning. The study recommends a hybrid approach that combines terrestrial infrastructure with satellite connectivity to enhance the effectiveness of BCP for ISPs in Indonesia.